missMethyl: an R package for analyzing data from Illumina’s HumanMethylation450 platform - Phipson, Belinda; Maksimovic, Jovana; Oshlack, Alicia (Bioinformatics (Oxford, England), 2016)
DNA methylation is one of the most commonly studied epigenetic modifications due to its role in both disease and development. The Illumina HumanMethylation450 BeadChip is a cost-effective way to profile >450 000 CpGs across the human genome, making it a popular platform for profiling DNA methylation. Here we introduce missMethyl, an R package with a suite of tools for performing normalization, removal of unwanted variation in differential methylation analysis, differential variability testing and gene set analysis for the 450K array. Availability and implementation: missMethyl is an R package available from the Bioconductor project at www.bioconductor.org. Contact:  alicia.oshlack@mcri.edu.au Supplementary information:  Supplementary data are available at Bioinformatics online.